2022
DOI: 10.1007/s10343-022-00780-6
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Dormancy and Enhancing Germination of Avena sterilis L. and Amaranthus retroflexus L. Weeds by Gibberellic Acid and Potassium Nitrate to Keep Soil and Crops Healthy

Abstract: Soils infested with weed seeds are considered hostile lands for crop production. In this context, great wild oat (Avena sp.) in winter seasons and redroot pigweed (Amaranthus sp.) in summer seasons represent problematic weeds in cropland fields. In a series of laboratory trials, we estimated the effects of gibberellic acid (GA3) and potassium nitrate (KNO3) on germination and seedling growth of Avena sterilis L. and Amaranthus retroflexus L. Different concentrations of GA3 and KNO3 were evaluated in randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Our data revealed that both cold stratification and application of more than 500 ppm of gibberellic resulted in the germination of all the examined Redroot pigweed seeds. These findings are consistent with existing data on the effects of gibberellic acid on germination in Redroot pigweed (Rizk et al., 2023 ). The efficacy of cold stratification and exogenous gibberellic acid for breaking dormancy is well documented in various plant species (Finch‐Savage & Leubner‐Metzger, 2006 ; Holdsworth et al., 2008 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data revealed that both cold stratification and application of more than 500 ppm of gibberellic resulted in the germination of all the examined Redroot pigweed seeds. These findings are consistent with existing data on the effects of gibberellic acid on germination in Redroot pigweed (Rizk et al., 2023 ). The efficacy of cold stratification and exogenous gibberellic acid for breaking dormancy is well documented in various plant species (Finch‐Savage & Leubner‐Metzger, 2006 ; Holdsworth et al., 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…While buried Redroot pigweed seed can remain viable for 6–10 years (Costea et al., 2004 ), we feel the nondeep physiological classification is appropriate as seeds with deep physiological dormancy are unaffected by the application of gibberellic acid and they frequently require more than 3 months of cold stratification before germination is promoted (Baskin & Baskin, 2004 ). Moreover, others have reported that Redroot pigweed primary dormancy can be altered by various laboratory processes such as after‐ripening (Enayati et al., 2019 ; Schonbeck & Egley, 1980 , 1981a ), incubation at different temperatures (Enayati et al., 2019 ; Gallagher & Cardina, 1998 ; Lawrence et al., 2004 ; Oryokot et al., 1997 ; Peiguo & Al‐Khatib, 2003 ; Schonbeck & Egley, 1981a , 1981b ), exposure to light with responses relayed via phytochrome‐mediated signaling (Gallagher & Cardina, 1998 ; Schonbeck & Egley, 1980 , 1981b ; Taylorson, 1970 ), treatment with nitrate or nitric oxide, potassium nitrate, ethylene, and gibberellic acid (Gallagher & Cardina, 1998 ; Kępczyński et al., 2017 ; Kępczyński & Sznigir, 2013 ; Rizk et al., 2023 ; Schonbeck & Egley, 1980 , 1981a , 1981b ), sulfuric acid (Santelmann & Evetts, 1971 ) or differences in water potential (Gallagher & Cardina, 1997 ; Oryokot et al., 1997 ; Schonbeck & Egley, 1980 , 1981b ). However, treatments involving acetone, carbon dioxide, sodium hypochlorite, or potassium nitrate were unable to change dormancy in this species (Santelmann & Evetts, 1971 ; Schonbeck & Egley, 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it plays an important role as an enzyme activator in photosynthetic activity. Immersion helps ensure that water and hormones in the KNO3 liquid can reach the seed and promote embryo growth without harming the embryo itself, which further increases the germination rate [15,16]. This study aims to determine the germination response of rattan jernang seeds (Daemonorops didymophylla Becc.)…”
Section: Introductionmentioning
confidence: 99%